The Impact of Infrastructure Escalation on Services and Economic Growth in Southern East Java - Angga Trie Sugiarto Wibowo; V. Rudy Handoko; Achluddin Ibnu Rochim (Eduvest - Journal of Universal Studies, 2023)
The purpose of this study is to determine the efforts to improve infrastructure in services and economic growth as well as to determine the impact of increased infrastructure on services and economic growth. The results showed that efforts to improve infrastructure in services and economic growth one of them is the realization of the construction of the Southern Cross Line (JLS). JLS is included in one of the efforts to improve infrastructure in services and economic growth, especially in the southern part of Java. JLS development is a national project. JLS is part of the construction of the south coast of Java Road (Pansela), starting from Pacitan, Trenggalek, Tulungagung Blitar, Malang, Lumajang, Jember and Banyuwangi. The results also show that through the construction of the Southern Cross Line (JLS) is expected to improve services and economic growth, especially economic growth in the southern part of Java considering the income and economic inequality between Southern and Northern Java. The southern part of Java can be categorized as poor, given the limited access to infrastructure.